Biogenic regions of cyanobacterial thylakoids form contact sites with the plasma membrane - Rast, Anna; Schaffer, Miroslava; Albert, Sahradha; Wan, William; Pfeffer, Stefan; Beck, Florian; Plitzko, Jürgen M.; Nickelsen, Jörg; Engel, Benjamin D. (Nature plants, 2019)
The three-dimensional architecture of the cyanobacterium Synechocystis was determined by in situ cryo-electron tomography. The tips of multiple thylakoids merge and contact the plasma membrane, performing a specialized biogenic function.